ANALISIS PERILAKU MINAT WISATAWAN BERKUNJUNG KEMBALI KE PULAU SAMOSIR - Simarmata, Asianna Martini; Panggabean, Fitri Yani; Pane, Yonson; Nainggolan, Elisabeth (Jurnal Ilmiah Dinamika Sosial, 2021)
Samosir Island is one of the leading tourist destinations in the Toba Caldera Geopark area. So many factors are related to the intention of tourists revisiting Samosir Island. So the research aims to prove: 1) the influence of tourist attraction and service quality on interest in reintention visiting Samosir Island; and 2) its influence through visitor satisfaction as an intervening. A total of 274 local tourists responded to a questionnaire distributed directly with the support of the Tourism Office of Samosir Regency and students. Collected data using a questionnaire that has been valid and reliable. The research team periodically collects information from tourists visiting Samosir Island, which takes about two months. The data analysis technique uses path analysis with the SPSS application. Research findings reveal that tourist attraction, service quality, and visitor satisfaction affect the reintention of tourists to Samosir Island. Service quality is the dominant predictor in the regression model. However, visitor satisfaction is not effective as an intervention that strengthens the intention of tourists to visit again. The implication of this paper is that visitor satisfaction needs to be improved by providing various facilities and infrastructure that support the optimization of service quality on Samosir Island. Thus providing a domino effect on increasing tourist visits to Samosir Island. Keywords: reintention,  tourist attraction, service quality, visitor satisfaction.